S100 Calcium Binding Protein A10, A Novel Oncogene, Promotes the Proliferation, Invasion, and Migration of Hepatocellular Carcinoma - Zhou, Xing; Shi, Min; Cao, Jun; Yuan, Tianwen; Yu, Guanzhen; Chen, Ying; Fang, Wenzheng; Li, Hongwei (Frontiers in Genetics, 2021)
Hepatocarcinogenesis is a highly complicated process that is promoted by a series of oncogenes. Our study aims to identify novel oncogenes promoting hepatocellular carcinoma (HCC) by bioinformatic analysis and experimental validation. Here, we reported that S100 calcium binding protein A10 (S100A10) was screened out as a potential novel oncogene in HCC by integrated analysis of OEP000321 dataset and the Cancer Genome Atlas (TCGA)-Liver-Cancer data. Furthermore, S100A10 was highly expressed in HCC samples and observably associated with patients’ overall survival (OS). Overexpression of S100A10 in Hep3B and Huh-7 increased the cell proliferation, whereas downregulation of S100A10 in SK-Hep-1 and HepG2 cells reduced the cell viability to almost stop growing. In vivo tumor growth assays showed that S100A10-overexpressing Hep3B cells had a larger tumor size than control. Moreover, S100A10 overexpression promoted Hep3B cells migration and invasion, and S100A10 knockdown inhibited SK-Hep-1 cells migration and invasion, in vitro. In conclusion, it is demonstrated that S100A10 is a novel oncogene in HCC, indicating a possible novel therapeutic strategy of HCC.